The protection of the Baltic Sea marine environment from land-based pollution in light of international and EU legal frameworks - Spivakova, Elizaveta (Riga Graduate School of Law, 2020)
The following thesis focuses on the legal mechanisms and norm adopted within the EU and international legal frameworks in order to protect the Baltic Sea marine environment from land-based pollution. As the Baltic Sea is one of the most polluted seas in the world, the specific and strong actions are crucially needed in order to restore the good ecological status of its marine environment. Thus, the main objective of the study is to determine whether the current international, regional and EU legal mechanisms are stringent enough in order to contribute to the Baltic Sea land-based pollution prevention. In case not, what are their limits. The course of the study revealed that existing legal mechanisms are mostly of a general nature and States are often unwilling to limit their level of discretion, thus, are reluctant to agree on a more stringent actions and mechanisms on an international and EU levels.
Keywords: Environmental law; Baltic Sea